Roteiros turísticos no espaço rural : estudo de caso do roteiro de turismo rural caminho pomerano em São Lourenço (RS), Brasil - Spindler, Magda Micheline (My University, 2014)
This research is focused on identifying how tourist routes are created in rural areas, based on the experience of the Roteiro de Turismo Rural Caminho Pomerano, São Lourenço do Sul (Rio Grande do Sul, Brazil). The investigation was accomplished by a bibliographic and field research. Among all techniques used for the data gathering, there were the interviews and participant’s observation. This case study is distinguished by its ethnographic bias. The theoretical reference approaches the cultural history of Pomeranian Immigrants, rural tourism, cultural manifests and tourist route and also present specific aspects about the Roteiro de Tursimo Rural Caminho Pomerano The main economic activity for São Lourenço do Sul is agribusiness. Throughout the decades of the 20th century, polycultures were substituted by tobacco monoculture. However, the apprehension of environmental and population health, in result of degrading elements from this culture fomented an increase of value in rural areas, intermediated by non-agribusiness activities such as tourism in rural areas, implemented in the city after year 2000. Now days, the route is made of six rural properties. The results for this implementation were both positive and negative: the valorization of cultural and historic aspects of pomeranos made possible to improve self-esteem and perpetuation of the route’s members, however the economic value increase is partial due to the discontinued income generation.
A presente pesquisa busca identificar como ocorre a roteirização turística no espaço rural, tendo por base a experiência do Roteiro de Turismo Rural Caminho Pomerano, no município de São Lourenço do Sul (RS, Brasil). A investigação é composta por pesquisas bibliográfica e de campo. Entre as técnicas utilizadas para a coleta dos dados estão as entrevistas e observação participante. A pesquisa diferencia-se por seu viés etnográfico. O referencial teórico versa sobre a história e cultura dos imigrantes pomeranos, turismo rural, manifestações culturais e roteiro turístico, além de apresentar especificidades sobre o Roteiro de Turismo Rural Caminho Pomerano. São Lourenço do Sul tem na agropecuária sua principal atividade econômica. Ao longo das últimas décadas do século XX, substituiu as policulturas pela monocultura de fumo. Contudo, a apreensão com a saúde da população e do meio ambiente, em decorrência de elementos degradadores oriundos dessa cultura fomentou a revalorização do espaço rural, por intermédio de atividades não agrícolas como o turismo no espaço rural, implantado no município a partir dos anos 2000. O roteiro é composto atualmente por seis propriedades rurais. Os resultados da implantação são tanto positivos quanto negativos: a valorização dos aspectos históricos e culturais pomeranos possibilitou maior autoestima e perpetuação do legado aos integrantes do roteiro, contudo a revalorização econômica é parcial, visto que a geração de renda proveniente da atividade turística é descontinuada.
Keywords: Turismo rural; Turismo -- Rio Grande do Sul; Turismo -- São Lourenço do Sul (RS); Fazendas -- uso recreativo